Regulation of an IMP Dehydrogenase Gene and Its Overexpression in Drug-sensitive Transcription Elongation Mutants of Yeast - Shaw, Randal J. (2001)
IMP dehydrogenase is a rate-limiting enzyme involved in the synthesis of GTP. In mammalian cells it is regulated with respect to growth rate and is the target of numerous therapeutic agents. Mutations in the RNA polymerase II elongation machinery render yeast sensitive to inhibitors of IMP dehydrogenase and defective in inducing transcription of one of the IMP dehydrogenase-encoding genes, IMD2. Here we show that loss of IMD2, but not IMD1, IMD3, or IMD4, conferred upon yeast the same drug sensitivity found in elongation mutants. We tested whether the drug sensitivity of elongation mutants is due to their inability to induce IMD2 by providing them with exogenous copies of the gene. In some elongation mutants, overexpression reversed drug sensitivity and a transcriptional defect. Overexpression in mutants with a more severe phenotype partially suppressed drug sensitivity but was inconsequential in reversing a defect in transcription. These findings suggest that the drug sensitivity of elongation mutants is largely but not solely attributable to defects in the ability to induce IMD2, because transcription is compromised even when IMD2 mRNA levels are adequate. We describe two DNA sequence elements in the promoter of the gene that regulate it. We also found that IMD2 mRNA abundance is coupled to cell growth rate. These findings show that yeast possess a conserved system that gauges nucleotide pools and cell growth rate and responds through a uniquely regulated member of the IMD gene family.